KONSELING INDIVIDUAL OLEH GURU BK BAGI PESERTA DIDIK MEMBOLOS DI SMPN 3 SUNGAI RAYA - Nur Halimah; Indri Astuti; Luhur Wicaksono (Universitas Tanjungpura, 2019)
AbstractResearchers want to know the implementation of individual counseling by guidance and counseling teachers for truant learners. Research problem is